2020
DOI: 10.4187/respcare.07536
|View full text |Cite
|
Sign up to set email alerts
|

COPD Overdiagnosis and Its Effect on 30-Day Hospital Readmission Rates

Abstract: BACKGROUND: Although specific guidelines exist for diagnosing COPD on the basis of spirometry testing data (FEV 1 /FVC < 0.70 or above the lower limit of normal), the literature suggests that overdiagnosis is common. Whether overdiagnosis increases 30-d readmission rates has not yet been explored. The objective of this study was to determine the prevalence of COPD overdiagnosis and its effect on 30-d hospital readmission rates in our institution. METHODS: We retrospectively identified all subjects who were cod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The possibility of misdiagnosis cannot be completely excluded because COPD is confirmed only by medical diagnosis. 43 Additionally, we did not include an objective index to assess the severity of the disease at the time of index admission. Because COPD severity is unknown, this can also affect the overall conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of misdiagnosis cannot be completely excluded because COPD is confirmed only by medical diagnosis. 43 Additionally, we did not include an objective index to assess the severity of the disease at the time of index admission. Because COPD severity is unknown, this can also affect the overall conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, hospital managers can use the model to recognize the conditions where more improvement is needed, which is an advancement upon other recent literature focusing on treatment plans of a single health condition [37]. Some studies have also investigated only one of the six health conditions for hospital readmissions [27,50]. The SM model provides an opportunity to efficiently allocate resources to health conditions with higher readmission probabilities than the mean peer group to reduce the risk of readmission.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that using teach-back education can reduce 30-day readmission rates. 3,7,8 Hospital readmissions are an important quality indicator for hospitals across the US; decreasing the rate of readmissions can result in an enormous cost-saving for a relatively inexpensive intervention. Most important, when quality care is provided, patient outcomes improve, and patient safety increases.…”
Section: Repeated Learningmentioning
confidence: 99%